2010
DOI: 10.3945/jn.110.124149
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Sensitivity to Cholecystokinin in Male Rats Fed a High-Fat Diet Is Reversible

Abstract: Adult rats chronically fed a high-fat (HF) diet maintain reduced sensitivity to cholecystokinin (CCK). We hypothesized that, similar to adult rats, pups fed a HF diet would also exhibit reduced sensitivity to CCK. To test this, male pups fed low-fat (LF) and HF isoenergetic (16.2 kJ/g) diets were administered CCK intraperitoneally (0.125-1 microg/kg) 1 wk following dietary adaptation. After receiving 0.5 microg/kg CCK, pups fed the HF diet suppressed food intake less (8.9 +/- 5.0%) than pups fed the LF diet (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 56 publications
1
27
0
1
Order By: Relevance
“…Indeed, there is an inverse correlation between detection of oleic acid and BMI, and hyposensitivity to oleic acid is associated with increased energy intake and BMI [69]. Furthermore, we and others have shown that rats maintained on HF diet exhibit increased avidity for concentrated oil solutions compared to LF fed controls during brief access lick tests [70][71][72]. Therefore, it is plausible that long-term exposure to HF diet leads to oral taste desensitization, possibly through decreases in lipid-activated Release of neurotransmitters via LCFA activation by taste receptor cells is mediated by CD36 and possibly GPR40 and GPR120 through yet unknown mechanisms.…”
Section: Hf Feeding Modulates Oral and Intestinal Sensing Of Lipidsmentioning
confidence: 87%
See 1 more Smart Citation
“…Indeed, there is an inverse correlation between detection of oleic acid and BMI, and hyposensitivity to oleic acid is associated with increased energy intake and BMI [69]. Furthermore, we and others have shown that rats maintained on HF diet exhibit increased avidity for concentrated oil solutions compared to LF fed controls during brief access lick tests [70][71][72]. Therefore, it is plausible that long-term exposure to HF diet leads to oral taste desensitization, possibly through decreases in lipid-activated Release of neurotransmitters via LCFA activation by taste receptor cells is mediated by CD36 and possibly GPR40 and GPR120 through yet unknown mechanisms.…”
Section: Hf Feeding Modulates Oral and Intestinal Sensing Of Lipidsmentioning
confidence: 87%
“…These changes in responses to CCK are reversible. For example, in-vitro desensitization of CCK that occurs very rapidly is reversed within minutes [149], while loss or restoration of CCK-8 sensitivity in in-vivo take two and three weeks, respectively [72].…”
Section: Hf Feeding Modulates Cck Responsesmentioning
confidence: 99%
“…It has been well described that adult rats chronically fed a high-fat diet maintain reduced sensitivity to CCK. Swartz et al50 demonstrated that male rat pups fed a high-fat diet exhibit reduced sensitivity to CCK; the development of this reduced sensitivity is quicker than its extinction when the high-fat diet was switched to a low-fat diet.…”
Section: Obesity-inducing Factorsmentioning
confidence: 99%
“…We effectively found that CCK-1R immunoreactivity was significantly lower in nodose ganglia of LP rats compared to control rats probably contributing to the resistance to CCK. A reduced sensitivity to a satietogenic dose of CCK, leading to hyperphagia, has already been shown in obesity-prone rats receiving standard chow (39) as well as in high-fat diet fed rats (40). In diet-induced obese rats, neurochemical analysis of VAN supports a vagal resistance to CCK and leptin in this model in which hyperphagia occurred concomitantly with this resistance (29).…”
Section: Discussionmentioning
confidence: 96%